(untitled) (International Journal of Engineering and Computer Science, 2015)
Reversible data hiding is the technique in which data in the cover image reversibly can retrieve after the extraction of hidden data in it. The technique provides the secrecy for a data, and also for its cover image. Ancestor methods of reversible data hiding were vacates room for data hiding after encryption, which leads to some errors at the time of data extraction and image recovery. Here describes a novel method of reversible data hiding in which, Reserving room before encryption in images, so that image extraction is subjected to free of errors. Here we are proposing an LSB plane method for the data hiding, which will result more space for embedded secret data. Moreover the usage of colour images as cover images will helps to store more data in different channels.